Extraction of antioxidant compounds from dovyalis: mixtures of ethanol and water - Cordeiro, Noélle Khristinne; Ristau, Ana Carolina Pinguelli; Braga, Gilberto Costa; Fernandes da Silva, Daniel; Villa, Fabíola; Soares de Vasconcelos, Edmar (Scientia Agraria Paranaensis, 2022)
Ethanol/water 80/20 has been the most suitable solvent mixture for the extraction of antioxidant compounds from fruits. However, the efficiency of the extraction solvent varies with the polar affinity of the different chemical compounds found in plant species. The objective of this work was to determine the efficiency of extraction of antioxidant compounds from the pulp and peel of dovyalis using ethanol/water mixtures as extracting solvent. Dried and ground pulp and peel were extracted with mixtures of ethanol/water solvents 100/0, 75/25 and 50/50 (v/v). Antioxidant activity (DPPH, ABTS and FRAP), total phenolic compounds and total flavonoids of the extracts were determined. The results showed that the 50% and 75% ethanol/water mixtures showed more efficient extraction of total phenolic compounds from the pulp and peel than 100% ethanol. The same trend was observed in the determinations of the antioxidant activities DPPH in the peel, ABTS in the pulp and FRAP in both fractions of the fruits, where the solvents 50% and 75% ethanol were superior to the 100% ethanol. In the extraction of flavonoids from the pulp and skin of the fruits, 50% ethanol was more efficient compared to the other solvent mixtures. The same was verified in the determination of the DPPH antioxidant activity in the pulp and ABTS in the peel of dovyalis fruits, that is, 50% ethanol was also superior to the other solvents. The 50% ethanol/water mixture was the most efficient solvent in the extraction of antioxidant compounds from the pulp and bark of dovyalis.